Results of Cultural Adaptation of Cognitive Stimulation Therapy (CST) for Elderly and Old Age People with Cognitive Impairment in Russia - A.A. Shvedovskaya; I.F. Roshchina; M.V. Kalantarova; A.I. Khromov (Клиническая и специальная психология)
Background. In Russia, the problem of maintaining cognitive well-being at a later age and helping elderly patients with dementia is an urgent task in the areas of healthcare and social protection of the population. The dynamics of the demographic situation in the country shows that by 2030, the older generation will make up almost a third of the population. At the same time, Russia is among the countries with the largest number of people with dementia. The aim of this study was the cultural adaptation of the Cognitive Stimulation Therapy (CST) program for elderly people with cognitive decline and dementia in a Russian-speaking sample with a pilot study of the use of CST in residential institutions on a group of elderly people with mild dementia. Methods. Cultural adaptation of the program was carried out within the framework of the Formative Method for Adapting Psychotherapy (FMAP) approach. The study used the official Russian translation of the manual for specialists conducting group classes “Making a Difference.” The sample consisted of several groups: (a) specialists (psychologists, medical workers, social workers) who participated in surveys with the aim of cultural adaptation of the management and procedure of the CST program, as well as receiving feedback after its implementation (n=25); (b) elderly people who participated in surveys for the purpose of cultural adaptation of stimulus material for the CST program (n=60, age 55–81 years (M=67.6, SD=6.2)); (c) elderly people with mild cognitive decline who participated in the pilot implementation of the CST program (n=5, age 68—83 years (M=75.8), MMSE and MoCA (n=5, M = 24.8 and 21.6, SD = 0.4 and 2.5, respectively). Six surveys were conducted: three in the form of face-to-face group discussions, two in the form of individual interviews, one survey was conducted online. Directed observation of the participants of the pilot study was also conducted (monitoring of progress, monitoring of support). The results are presented within the framework of the five stages of FMAP according to the “bottom-up” principle applied to the CST intervention. Results of surveys and observations received during the pilot study regarding feedback from program participants, staff of a residential facility for elderly patients with cognitive deficits, and group leaders were analyzed. Conclusions. The basic principles, structure of the intervention program and activities proposed in the CST manual are acceptable for use with Russian-speaking elderly people with mild dementia. The “Making a Difference” manual, translated into Russian and culturally adapted, is ready for use and further large-scale implementation of the intervention. The prospects for the study include assessment of effectiveness of CST on a Russian sample in various conditions (in the process of implementation), as well as development an online version of CST for the elderly population.